Education Program that Integrates Da'wah, Language and Arts Based on Da'wah in Cindaga Village, Banyumas Regency - Muhammad Ash-Shiddiqy; Nawawi; Muridan (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025)
Cindaga Village, Banyumas Regency, is characterized by rich cultural traditions and religious diversity, which simultaneously serve as opportunities and challenges in maintaining social harmony. To address this, an educational program was developed that integrates da'wah, language, and arts through the Asset-Based Community Development (ABCD) method. This study employs a mixed-methods approach, combining both quantitative and qualitative techniques. Quantitative data were collected through surveys measuring community participation and perceptions of religious moderation, while qualitative data were obtained through interviews, participant observation, and documentation of cultural activities. The findings show that the integration of karawitan (traditional Javanese gamelan music) with da'wah-based education not only preserves cultural heritage but also serves as a medium for cultural da'wah that promotes tolerance, justice, and balance. Furthermore, the ABCD method effectively mobilized local assets and community engagement across generations, strengthening cultural identity, enhancing social cohesion, and fostering collective awareness of the importance of peaceful coexistence in diversity.